A systematic review of humor employed in teaching English as a second language in Asia - Tianli, Zhou; Mansor, Nor Shahila; Liu, Guoqiang; Junhua, Peng (SAGE Publications Inc., 2024)
In recent times, the number of studies examining the use of humor in teaching English as a second language (ESL) in Asian countries has increased as researchers have acknowledged the positive effects that humor has on language teaching. This study presents a systematic review focused on the use of humor in ESL teaching within Asian countries. Its objectives are to acquire comprehensive knowledge of the current research status, research participants and methods, and research perspectives, and to examine the outcomes of incorporating humor into ESL instruction in Asian contexts in order to pinpoint research gaps for future studies. This study included the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (2020). Moreover, 35 articles relevant to the use of humor in Asian ESL teaching were identified as of the date when this study was conducted. After performing content analysis, the findings revealed that the first related articles in Asia were published in 2009, after which more and more articles emerged. These studies took place in 14 Asian countries, with most of them focusing on Turkey, Iran, and Indonesia. In addition, they involve diverse research methods and perspectives, whilst most of the participants are university students. This suggests that humor is more suitable for use when teaching high-proficiency English learners. Moreover, humor is a double-edged sword that has positive and negative impacts on ESL teaching in Asian countries. Finally, a number of recommendations for future studies have been proposed in this study.